Manage your time better (Chicago, IL : JWA Video, 2002)
Training program shows how to virtually "add" minutes to each day for forming a logical, prioritized sequence or "plan of action" that incorporates the use of symbols, notes, teamwork, clear communication processes, and much more.
Keywords: Time management